Spectral shapes of second-forbidden single-transition nonunique β decays assessed using the nuclear shell model - Ramalho, Marlom; Suhonen, Jouni; Neacsu, Andrei; Stoica, Sabin (Frontiers in Physics, 2024)
Experimental and theoretical studies of β electrons (electrons emitted in β –decay transitions) and their β-electron spectra have recently experienced a rapid expansion. These β spectral shapes have been used to study total β spectra of fission-product nuclei in the quest for explanation of the reactor-flux anomalies, and individual β transitions in search for β spectral shapes sensitive to the effective value of the weak axial coupling g A . In the former case the TAGS (total absorption gamma-ray spectroscopy) can be efficiently used to measure the total β spectral shapes and in the latter case dedicated measurements of the involved forbidden nonunique β transitions have been deployed. The fourth-forbidden nonunique decay transitions 113 Cd(1/2 + g.s. ) → 113 In(9/2 + g.s. ) and 115 In(9/2 + g.s. ) → 115 Sn(1/2 + g.s.) represent theoretically and experimentally much-studied cases where the total β spectra consist of these single transitions.In these particular cases the TAGS method could be used to assess the effective value of g A . In the present work we have identified five more interesting cases where a total β spectrum consists of a single transition. These spectra correspond to second-forbidden nonunique transitions and are g A and/or sNME dependent, where sNME denotes the so-called small relativistic vector nuclear matrix element. These studies have been performed using the nuclear shell model with well established effective Hamiltonians. With this we target to β transitions that would potentially be of high interest for the TAGS and present and future dedicated β-spectrum experiments.